2003
DOI: 10.4049/jimmunol.171.6.3216
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft Localization of Cell Surface E-Selectin Is Required for Ligation-Induced Activation of Phospholipase Cγ

Abstract: E-selectin, an endothelial cell surface adhesion receptor for leukocytes, also acts as a signaling receptor. Upon multivalent ligation, E-selectin transduces outside-in signals into the endothelium leading to changes in intracellular Ca(2+) concentration and activation of the mitogen-activated protein kinase signaling pathway. In addition, following leukocyte engagement, E-selectin associates via its cytoplasmic domain with components of the actin cytoskeleton and undergoes alterations in phosphorylation state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 55 publications
4
58
1
1
Order By: Relevance
“…These domains may propagate signals into endothelial cells that regulate later events in the inflammatory cascade. 27 Our results, in conjunction with previous studies, underscore the importance of particular cell surface presentations of selectins or their ligands during leukocyte rolling on vascular surfaces under flow. Unlike several other adhesion receptors, P-selectin and E-selectin undergo rapid internalization from the cell surface.…”
Section: E-selectin Clusters In Membrane Domainssupporting
confidence: 73%
See 2 more Smart Citations
“…These domains may propagate signals into endothelial cells that regulate later events in the inflammatory cascade. 27 Our results, in conjunction with previous studies, underscore the importance of particular cell surface presentations of selectins or their ligands during leukocyte rolling on vascular surfaces under flow. Unlike several other adhesion receptors, P-selectin and E-selectin undergo rapid internalization from the cell surface.…”
Section: E-selectin Clusters In Membrane Domainssupporting
confidence: 73%
“…This observation differed from a previous report that virtually all E-selectin was in lipid rafts of HUVECs. 27 That report used a detergent-free procedure in which sonicated cell membranes were fractionated on a discontinuous sucrose gradient, as originally used to isolate caveolae. 47 In this procedure, nonraft components might float in more buoyant fractions if they associate with raft structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our use of a panel of enzymespecific inhibitors suggested that this signal is mediated through the classic phospholipase C (PLC)-IP 3 pathway (24), and involves Src, which may bridge MUC1 with calcium signal mediators, as Src reportedly physically associates with MUC1 (5) and can be upstream of PI 3-kinase and PLC␥ (25)(26)(27). The data showing the dependence of this signal on lipid rafts is complementary, as cholesterol depletion has previously been shown to disrupt the function of Src (28) and PLC (29,30).…”
Section: Discussionsupporting
confidence: 49%
“…Recently, it was reported that in cultured endothelium, E-selectin is localized in membrane lipid rafts and that, on ligation, E-selectin clusters and redistributes in a caveolin-1-rich plasma membrane fraction. 6 The Weibel Palade bodies, considered initially as storage and secretory granules for von Willebrand factor (vWf), are now reported to deposit also P-selectin, IL-8, eotaxin-3, endothelin-1, and angiopoietin-2; the regulated exocytosis of these bioactive components play a role in inflammation, hemostasis, and vascular tone. 7 Furthermore, the ECs that constitute a mass of Ϸ1 kg spread throughout the body (estimated total area of Ϸ7000 m 2 Ϸ6ϫ10 13 cells) possess an innate heterogeneity, expressed by differences in their structure and function according to the vessel they are lining or tissues in which they reside.…”
mentioning
confidence: 99%